Peran TikTok sebagai Platform Promosi Digital dalam Mendorong Intensi Pembelian Produk Kuliner Lokal - Ni Komang Mela Tri Utari; Esa Setiawati; Ni Luh Laksmi Rahmantari; I Putu Dharmawan Suryagita Susila Putra; I Gusti Ayu Lia Yasmita (Universitas Hayam Wuruk Perbanas, 2025)
This study aims to analyze the role of TikTok as a digital promotion platform in encouraging purchase intention toward local culinary products at the MSME Es Teler Tidar Sukodono. The development of digital technology has significantly transformed consumer behavior, particularly in the process of information searching and purchasing decision-making. This study employs a descriptive approach using a mixed-method design, combining qualitative data obtained through interviews and observations with quantitative data collected through questionnaires distributed to 50 respondents. The data were analyzed using descriptive percentage techniques and qualitative interpretation. The results indicate that promotion through TikTok achieved an average score of 94.24%, which falls into the “very feasible” category. This finding suggests that TikTok is effective in increasing consumer purchase intention. Furthermore, interview results reveal that engaging visual content, the use of trends, and interactive features on TikTok are able to enhance product attractiveness and influence purchasing decisions.